From Texts to Travel: A Multidisciplinary Approach to Healing through Literature and Tourism - Rosmaria Rosmaria (PT. AVID MEDIA INDONESIA, 2025)
This article investigates the intersection of literature and tourism as multidimensional avenues for psychological healing, educational growth, and cultural continuity. Drawing on a multidisciplinary review of studies published between 2010 and 2025, it analyzes bibliotherapy and healing tourism through the lenses of psychology, education, and cultural studies. Literature, particularly in the form of bibliotherapy, fosters catharsis, emotional regulation, and resilience by allowing readers to process trauma and reframe personal experiences. Tourism, especially wellness and cultural tourism, provides embodied experiences of renewal and identity reformation through intercultural encounters, heritage rituals, and narrative journeys. When combined, literature and tourism function as complementary narrative pathways inner journeys through texts and outer journeys through travel that cultivate empathy, reinforce cultural identity, and enhance socio-emotional learning. The study argues for integrating these modalities into interdisciplinary practices that connect mental health, education, and cultural preservation, offering a holistic model of well-being adaptable to diverse global and local contexts.